2015
DOI: 10.3732/ajb.1400285
|View full text |Cite
|
Sign up to set email alerts
|

Auxin activity: Past, present, and future

Abstract: Long before its chemical identity was known, the phytohormone auxin was postulated to regulate plant growth. In the late 1800s, Sachs hypothesized that plant growth regulators, present in small amounts, move differentially throughout the plant to regulate growth. Concurrently, Charles Darwin and Francis Darwin were discovering that light and gravity were perceived by the tips of shoots and roots and that the stimulus was transmitted to other tissues, which underwent a growth response. These ideas were improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(239 citation statements)
references
References 158 publications
(207 reference statements)
4
218
0
17
Order By: Relevance
“…A major challenge for auxin biologists is to explain how a small molecule such as IAA can trigger the vast range of intricate, complex, and tissue-specific responses throughout plant development (Paciorek and Friml, 2006;Teale et al, 2006;Benjamins and Scheres, 2008;Vanneste and Friml, 2009;Rademacher et al, 2012;Enders and Strader, 2015;Hagen, 2015). We have recently shown that the atypical auxin response factor ETT responds to changes in cellular auxin levels in a different way from the canonical TIR1-dependent auxin-signaling pathway (Simonini et al, 2016), thus providing an additional route for auxin to mediate its diverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for auxin biologists is to explain how a small molecule such as IAA can trigger the vast range of intricate, complex, and tissue-specific responses throughout plant development (Paciorek and Friml, 2006;Teale et al, 2006;Benjamins and Scheres, 2008;Vanneste and Friml, 2009;Rademacher et al, 2012;Enders and Strader, 2015;Hagen, 2015). We have recently shown that the atypical auxin response factor ETT responds to changes in cellular auxin levels in a different way from the canonical TIR1-dependent auxin-signaling pathway (Simonini et al, 2016), thus providing an additional route for auxin to mediate its diverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cohesion was characteristic for a callus with stable growth [37]. Moreover, the grey pigmentation present for all calli at 1.0 mg dm −3 2,4-D concentration may result from distinct cell hydration that is one of the characteristic effects of auxin action [38]; this is favorable for callus proliferation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin regulates a wide range of developmental processes, and tight control of auxin response is maintained by multiple modes of regulation. These include regulating auxin biosynthesis and metabolism, transport, and signaling (reviewed in Enders and Strader, 2015). To date, nuclear auxin signaling components have been well characterized (reviewed in Chapman and Estelle, 2009;Salehin et al, 2015).…”
mentioning
confidence: 99%